Peran Komunikasi Penyiaran Islam dalam Membangun Literasi Keagamaan Masyarakat - Salsabilla, Hanum; Azzahra, Nisa; Kusuma, Adhi; Tri Wijaya, Livia; Sumarni, Rini (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This article explores the role of Islamic broadcasting communication in enhancing religious literacy in the digital era, focusing on television, radio, and digital platforms such as YouTube, Instagram, and TikTok. Using a literature review and content analysis approach, the study finds that Islamic media broadcasting significantly contributes to disseminating moderate and inclusive Islamic values while reaching a broad, diverse audience across generations and regions. Digital da'wah that is adaptive, interactive, and grounded in narratives of tolerance has proven effective in countering misinformation and fostering interfaith dialogue. Participatory and inclusive communication strategies are key to building contextual and harmonious religious awareness in a pluralistic society. Thus, Islamic broadcasting media functions not only as an information provider but also as a social transformation agent promoting a religious, tolerant, and civilized society.